Analysis of the Utilization of Artificial Intelligence in Supporting Students Academic Activities - Mohamad Firman Kamsia; Arifin Arifin; Darmawan Thalib (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2026)
This study aims to analyze the use of Artificial Intelligence (AI) in supporting the academic activities of students in the Department of Educational Management, Gorontalo State University. The approach used is a quantitative descriptive explanatory study with a population of 480 active students from the 2019–2025 intake. The sample was determined purposively and applied a total sample, resulting in 191 students from the 2022–2023 intake becoming the study respondents. Data were collected through questionnaires and interviews, with validity tests using product moment correlation and reliability through Cronbach's Alpha (>0.70), indicating a feasible and reliable instrument. Descriptive percentage analysis was applied to assess students' needs for AI, its utilization, and its impact on academic activities. The results showed that students understood the AI ​​use policy, paid attention to data protection, and actively utilized AI to complete assignments, draft academic papers, search for and summarize references, and understand course material. The use of AI has a positive impact on learning effectiveness, assignment quality, independence, critical thinking skills, and student learning motivation. The study emphasized the need for ethical guidance, digital literacy, and regulation of AI use to ensure responsible use and support academic integrity. These findings can serve as a reference for developing AI strategies in higher education and further research on technology integration in learning.